Phonetically Grounded Structural Bias in Learning Tonal Alternations - Huang, Tingyu; Do, Youngah (Frontiers in Psychology, 2021)
This study investigates the hypothesis that tone alternation directionality becomes a basis of structural bias for tone alternation learning, where ‘structural bias’ refers to a tendency to prefer uni-directional tone deletions to bi-directional ones. Two experiments were conducted. In the first, Mandarin speakers learned three artificial languages, with bi-directional tone deletions, uni-directional, left-dominant deletions, and uni-directional, right-dominant deletions respectively. The results showed a learning bias toward uni-directional, right-dominant patterns. As Mandarin tone sandhi is right-dominant while Cantonese tone change is lexically restricted and does not have directionality asymmetry, a follow-up experiment trained Cantonese speakers either on left- or right-dominant deletions to see whether the right-dominant preference was due to L1 transfer from Mandarin. The results of the experiment also showed a learning bias toward right-dominant patterns. We argue that structural simplicity affects tone deletion learning but the simplicity should be grounded on phonetics factors, such as syllables’ contour-tone bearing ability. The experimental results are consistent with the findings of a survey on other types of tone alternation’s directionality, i.e., tone sandhi across 17 Chinese varieties. This suggests that the directionality asymmetry found across different tone alternations reflects a phonetically grounded structural learning bias.